DMEK graft: One size does not fit all. Issue 1 (24th June 2022) - Parekh, Mohit; Romano, Davide; Wongvisavavit, Rintra; Coco, Giulia; Giannaccare, Giuseppe; Ferrari, Stefano; Rocha‐de‐Lossada, Carlos; Levis, Hannah J.; Semeraro, Francesco; Calvo‐de‐Mora, Marina Rodríguez; Scorcia, Vincenzo; Romano, Vito
Abstract: Descemet membrane endothelial keratoplasty (DMEK) is a popular procedure for the treatment of corneal endothelial diseases mainly targeting Fuchs endothelial corneal dystrophy (FECD) and pseudophakic bullous keratopathy (PBK). Although DMEK has multiple advantages, it is challenging in terms of graft preparation and delivery. One of the crucial factors of DMEK graft preparation is determining the size of the graft. Evaluating risks and benefits of transplanting larger or smaller grafts compared with the descemetorhexis performed following a standard DMEK procedure thus becomes important. Advanced techniques like pre‐loaded DMEK requires pre‐selection of graft diameter without physical examination of the eye making it more challenging. Therefore, recognizing the benefits of graft size and the number of transplanted endothelial cells becomes essential. Smaller DMEK grafts have been preferred and accepted for grafting. Larger diameter grafts have advantages but can be challenging due to higher detachment rates. We thus aim to review the challenges of preparing and delivering DMEK tissues with small or large diameter based on selected descemetorhexis area, discuss the outcomes based on different graft sizes, highlight related complications and suggest which cases may benefit from adopting smaller or larger graft size.